The society of slaves and free blacks in the region of Piura Notes on social emancipation and politicization, 1780-1812 - Espinoza Claudio, César (2014)
In this essay we intend to explore interactions and prosecutions that lived black people in freedom and slavery, introducing us to the study of their daily life, manumission processes and social politization during the goverment of the Bourbons. For this purpose we review demographic size and composition, labor world, land struggles, meaning and importance of Afrodescendants legal proceedings to continue resisting the Spanish colonial state and legislation.